Water resources use optimisation in the Mediterranean basin - Caliandro A.; Rubino P.; Stellacci A.M. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
Agriculture uses about 60 per cent of the total available water resources but this amount is not sufficient to meet crop irrigation needs and it is going to decrease due to the growing demand for domestic and industrial uses. A strategy to increase water availability for the agricultural sector is to improve overall water use efficiency, on average lower than 50 per cent by increasing the value of the highest number of its components. In this paper, the main groups of factors affecting water use efficiency have been analysed, and some important actions to be adopted in order to increase the single components, have been described and supported by numerous experimental results. In particular, in relation to the engineering aspects, the importance of the correct dimensioning of the irrigation networks, of the water delivery on demand, of the definition of the variables relative to the irrigation method and of the water pricing per volume used, has been highlighted; in relation to the agronomic aspects, the role of the correct dimensioning of the irrigation variables of the evaluation of the interaction with other agronomical practices, of the adoption of controlled water stress and supplementary irrigation, has been stressed; finally, the importance of the crops choice in relation to their intrinsic water use efficiency to their response to irrigation water, crucial also together with the economic response to define the optimal allocation of the available water resources has been stated. In the end, some important research needs according to the authors have been reported.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)